‘The New Normal’ and the Strategies of Marketers to Attract Consumers - Chakraborty, Debarun; Dash, Ganesh (Indian Journal of Marketing, 2022)
In the middle of the pandemic, marketers are creating unique tactics to drive new demand, reorganize value chains, and deliver brand experiences. Marketers are grabbing the chance to rethink their fundamental marketing strategies in order to align with the new normal of marketing, which is digital evolution. The crucial question is how marketers can expand their marketing approach in the ‘New Normal.’ The perspective presents the various perspectives of marketers who are creating high impact, from designing innovative approaches to delivering the best customer experiences.